Experimental and modelling studies on thermodynamic methane hydrate inhibition in the presence of ionic liquids - Nashed, O. (Elsevier B.V., 2018)
This paper presents a series of experimental and modelling studies on the thermodynamic inhibition effects of four ionic liquids on the methane hydrate formation. The investigated ionic liquids are 1-methyl-3-octylimidazolium chloride MOIM-Cl, 1-methylimidazolium hydrogen sulfate H-MIM-HSO4, tetraethylammonium iodide TEA-I, and 1-hexyl-3-methylimidazolium iodide HMIM-I. The impact of 0.1 mass fraction concentration ionic liquids on the methane hydrate phase boundary was evaluated by measuring the dissociation temperature of methane hydrate in the pressure range of 5.1â11.1 MPa, using a high pressure differential scanning calorimeter. The molar dissociation enthalpy of methane hydrates was calculated using the ClausiusâClapeyron equation. The density was measured for 0.10 mass fraction of aqueous solutions of ionic liquids at 293.15 K, and then compared to the commercially available gas hydrate inhibitors. The results demonstrated that 1-methylimidazolium hydrogen sulfate H-MIM-HSO4 has the highest inhibitory performance among the four ionic liquids considered. Moreover, the Dickens and Quinby-Hunt (electrolyte) model was applied to predict the phase equilibrium data of the studied ILs. The predicted data is in agreement with the experimental data. Â© 2017